Crystallographic plane and topography-dependent growth of semipolar InGaN nanorods on patterned sapphire substrates by molecular beam epitaxy. Issue 46 (16th November 2018) - Shen, Jian; Zheng, Yulin; Xu, Zhenzhu; Yu, Yuefeng; Gao, Fangliang; Zhang, Shuguang; Gan, Yang; Li, Guoqiang
Abstract : A patterned sapphire substrate with exposed high-index crystallographic planes, with well-organized step-terrace structures, facilitates the growth of well-aligned semipolar InGaN nanorods. Abstract : A low-cost, high-efficiency, and catalyst-free method for fabricating well-aligned and uniform semipolar InGaN nanorods (NRs) by molecular beam epitaxy (MBE) is proposed using an optimized patterned sapphire substrate (PSS) with high Miller index crystallographic planes. The dense, obliquely aligned, and high-quality semipolar (11̄02) InGaN NRs are fabricated on hexagonal pyramid arrays of the PSS for the first time in this work. A unique semipolar (11̄02) and polar (0001) InGaN NR array composite structure is thus achieved on a hexagonal pyramid PSS. The connected, uniform, and obliquely aligned NRs are formed on the PSS with cylindrical arrays. The cylindrical and hexagonal pyramid arrays of PSSs are structured by the standard photolithography process and etching techniques. Both pattern topography and crystallographic plane of the PSS significantly affect the morphology, dimension, and crystallographic orientation of InGaN NRs. It is clearly demonstrated that the PSS with exposed high Miller index crystallographic planes, with well-organized step-terrace structures, facilitates the growth of ordered and dense semipolar InGaN NRs. This work contributes to the thorough understanding of the nucleation and growth mechanisms of InGaN NRs on a high Miller index plane of the PSS with different topographies, as well as of those of controllably fabricating dense and uniform semipolar NRs, thus facilitating the fabrication of NR-based optoelectronic devices with enhanced performance.